Mitis Iudex Dominus Iesus – nadzieje i obawy sądownictwa kościelnego w sprawach o nieważność małżeństwa - Nowakowski, Bartosz (Ius Matrimoniale, 2015)
The article reflects upon the question of modifications in canonical matrimonial processes caused by pope Francis’ motu proprio Mitis Iudex Dominus Iesus. Some of the issues brought up by the author are: changes of tribunals’ competences in matrimonial cases, collegiality of the tribunal, the sufficiency and enforceability of the sentence after the affirmative decision of the first instance and both the positive and negative effects of designing a briefer form of trying nullity cases called processus matrimonialis brevior coram Episcopo.